Scanning electron microscopy study of Lars Silén’s cheilostome bryozoan type specimens in the historical collections of natural history museums in Sweden - Martino, Emanuela Di (Zootaxa, 2023)
The type specimens of 42 cheilostome bryozoan species introduced by Lars Silén between 1938 and 1954 and housed at three different Swedish institutions (the Swedish Museum of Natural History in Stockholm, the Biological Museum in Lund and the Museum of Evolution in Uppsala) are here revised using scanning electron microscopy, with two exceptions, for the first time. As a result of this revision, new morphological observations were made for some species, such as ooecia in Antropora erecta, a costal pseudopore in Jullienula hippocrepis, intracolonial variation in the number of intracostal windows in Costaticella gisleni, and oral spines in Triphyllozoon mauritzoni. Some other observations confirmed the presence of structures/polymorphs in type material that had previously only been noted in non-type specimens, such as spinose interzooidal kenozooids in Retevirgula triangulata and putative brooding zooids in Bugulina kiuschiuensis. Structures originally interpreted as hydroid tube openings on the dorsal side of Triphyllozoon microstigmatum were confirmed to be avicularia, while the supposed kenozooidal attachment rootlet of Fedora nodosa might be the polypide tube of a coronate scyphozoan. In addition, the original combination Heliodoma goesi is here reinstated after Lagaaij assigned the species to Setosellina in 1963. The following new combinations are also proposed: Labioporella aviculifera for Siphonoporella aviculifera; Mangana canui and Mangana incrustata for Callopora canui and Tegella incrustata, respectively; Sphaerulobryozoon ovum for Fedora ovum. Lectotypes were selected when appropriate. This work clarifies the exact identity of some species that have never been recorded after their first description, such as Stylopoma magnovicellata and three species of Triphyllozoon, and contributes to the current increasing effort to digitize historical key specimens in natural history museum collections.